Does MBA Studies Increase the Value of Human Capital in the Labour Market? - Kateřina Bočková (UIKTEN, 2021)
Presented paper focuses on a research of added value of MBA studies organized at Academy of crisis management and management, Ltd. Uherské Hradiště on its graduates. The added value in this research is monitored in correlation to graduates’ career, recorded changes and also in correlation to the development of their knowledge and skills. Attention is also devoted to the returns of funds invested in these studies. The data are obtained thanks to a semistructured interview and a questionnaire survey among MBA graduates. They are processed by using mathematical-statistical methods, methods of comparison and analysis of information.